Pengaruh Media Booklet dan Ceramah Terhadap Pengetahuan WUS Tentang Kanker Serviks dan Pemeriksaan IVA - Dessy Hidayati Fajrin; Sari, Utin Siti Candra; Utami, Siti (Rena Cipta Mandiri, 2025)
Cervical cancer is one of the leading causes of death in women in Indonesia. Early detection through VIA (Visual Inspection with Acetic Acid) examination is an important step in prevention. However, the level of knowledge and motivation of women of childbearing age towards this examination is still low. Education through booklet media is one of the strategies that can increase understanding and encouragement to do the examination. This study used a quasy experimental method with a non-equivalent control group design approach. The Mann-Whitney test results showed a significant value of p<.001 (<0.05). which means there is a significant difference between the two groups. Education through booklet media has a significant effect on increasing the knowledge and motivation of women in conducting early detection of cervical cancer.